Synthesis, Structural, FT-IR and Non-Linear Optical Studies of Pure and Lanthanum Doped L-Arginine Acetate Single Crystals - GNANASEKARAN†, P.; MADHAVAN*, J. (Asian Journal of Chemistry, 2024)
Single crystals of pure and La3+ doped L-arginine acetate have been successfully grown from aqueous solution by slow evaporation technique. The grown crystals were confirmed by powder X-ray diffraction studies. The optical properties of the crystals were studied by FT-IR and UVVis- NIR spectral techniques and the influence of the La3+ is reported. The second harmonic generation efficiencies of the crystals were confirmed by Kurtz and Perry powder technique.